The myth of the 1-day training: the effectiveness of psychosocial support capacity-building during the Ebola outbreak in West Africa. (7th May 2019) - Horn, Rebecca; O'May, Fiona; Esliker, Rebecca; Gwaikolo, Wilfred; Woensdregt, Lise; Ruttenberg, Leontien; Ager, Alastair
Abstract : Background: In emergencies and resource-poor settings, non-specialists are increasingly being trained to provide psychosocial support to people in distress, with Psychological First Aid (PFA) one of the most widely-used approaches. This paper considers the effectiveness of short training programmes to equip volunteers to provide psychosocial support in emergencies, focusing particularly on whether the PFA training provided during the Ebola outbreak enabled non-specialists to incorporate the key principles into their practice. Methods: Semi-structured interviews were conducted in Sierra Leone and Liberia with 24 PFA trainers; 36 individuals who participated in PFA training; and 12 key informants involved in planning and implementing the PFA roll-out. Results: Findings indicate that many PFA training-of-trainers were short and rarely included content designed to develop training skills. As a result, the PFA training delivered was of variable quality. PFA providers had a good understanding of active listening, but responses to a person in distress were less consistent with the guidance in the PFA training or with the principles of effective interventions outlined by Hobfoll et al . Conclusions: There are advantages to training non-specialists to provide psychosocial support during emergencies, and PFA has all the elements of an effective approach. However, the very short training programmes which have been used to train non-specialists in PFA might be appropriate for participants who already bring a set of relevant skills to the training, but for others it is insufficient. Government/NGO standardisation of PFA training and integration in national emergency response structures and systems could strengthen in-country capacity.